Air Pollution in Kazakhstan and Its Health Risk Assessment - D. Kenessary; A. Kenessary; Z. Adilgereiuly; N. Akzholova; A. Erzhanova; A. Dosmukhametov; D. Syzdykov; Abdul-Razak Masoud; Timur Saliev (Ubiquity Press, 2019)
Background: Air pollution in Kazakhstan is caused by many factors and poses serious threats to public health. Ambient air in the cities of Kazakhstan is polluted due to mining and processing of mineral resources, oil and gas production, gasoline and diesel fuel motor vehicles, industrial enterprises. Objective: The study aim is to assess the air pollution degree in most significant settlements of Kazakhstan and define risk levels for the population health. Ambient air monitoring was conducted in 26 cities. Air pollution severity was assessed by the analysis results and processing of air samples taken at the stationary observation posts. Health risk assessment due to chemical factors was calculated according to the approved risk assessment methodology. Findings: There is high risk of acute adverse effects risk from suspended particles, oxides and dioxides of nitrogen and sulfur in almost all of the studied cities. The most unfavorable situation is in Ust-Kamenogorsk. Also, there is the adverse chronic effects risk caused by suspended particles exposure in majority of the studied cities. Extremely high chronic effects risk as a result of heavy metals exposure was detected in Ust-Kamenogorsk, Shymkent, Almaty, Taraz and Balkhash. Unacceptable carcinogenic risk levels have been determined for professional groups and the whole population with respect to cadmium in Shymkent, Almaty, Balkhash; arsenic in Shymkent, Almaty, Balkhash; lead in Taraz; chromium - in Shymkent, Aktobe, Almaty and Balkhash. Thus, the values of the hazard quotients and indices for acute and chronic exposure in most of the studied cities of Kazakhstan exceed the permissible level equal to 1.0. Conclusion: Due to the unacceptable risk levels in the cities it is strongly recommended to conduct a detailed study of the health status of the population depending on the air pollution.